2018
DOI: 10.1108/mhsi-07-2018-0022
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of online social support on the relationship between stress and mental well-being

Abstract: Purpose Workplace stress is on the rise and progressive organizations devise their own mechanisms to mitigate it and enhance mental wellbeing (MWB). Of late, the workforce is increasingly dependent on social networking sites (SNS) for social exchanges and debate is well documented if SNS could be used to mediate the relationship between stress and MWB. The purpose of this paper is to investigate this relationship. Design/methodology/approach This study is based on a survey of 269 employees, on the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…In line with the finding of this research, it was emphasized that in social media individuals could experience social support through active interactions such as texting and talking to people as well as passive interactions such as receiving likes and comments on photos or videos and having their shares reposted by someone else (McCloskey et al, 2015). In a study, it was highlighted that getting social support by other individuals on social media reduced the stress, loneliness and depression levels of the individuals and increased their well-being (Xavier, 2018). However, "misinformation and frightening news/shares" that caused a negative effect as a result of using social media during the pandemic were also mentioned.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In line with the finding of this research, it was emphasized that in social media individuals could experience social support through active interactions such as texting and talking to people as well as passive interactions such as receiving likes and comments on photos or videos and having their shares reposted by someone else (McCloskey et al, 2015). In a study, it was highlighted that getting social support by other individuals on social media reduced the stress, loneliness and depression levels of the individuals and increased their well-being (Xavier, 2018). However, "misinformation and frightening news/shares" that caused a negative effect as a result of using social media during the pandemic were also mentioned.…”
Section: Discussionmentioning
confidence: 60%
“…Suggestions made by World Health Organization (WHO) on what individuals can do to protect their mental health during the coronavirus pandemic (2020), it has been Onat Kocabıyık 448 emphasized that regular communication with close ones via telephone and online channels is important to maintain social communication. Similarly, in other studies, it was asserted that having social support on social media by both other individuals (Xavier, & Wesley, 2018) and governmental institutions (Cumiskey, & Hjorth, 2018;Westerman, Spence, & Van Der Heide, 2014) decreased individuals' stress and depression levels. In addition, it was emphasized that helping other individuals had a positive effect on mental health (WHO, 2020), and the important effect of social media calls for solidarity and helping each other on this issue was mentioned (Cumiskey, & Hjorth, 2018).…”
Section: Introductionmentioning
confidence: 62%
“…Furthermore, online social support is associated with stress coping and resilience (Chung et al, 2014); meanwhile, resilience and stress coping was associated with mental health (Yoo, 2019;Wu et al, 2020), life satisfaction (Buser and Kearney, 2017;Zheng et al, 2020) and well-being (Harms et al, 2018). Hence, previous studies have revealed that online social support is associated with an increase in well-being (Lee et al, 2013;Xavier and Wesley, 2018;Ali, 2020). As such, previous studies have confirmed the link between online self-disclosure and online social support (Lee et al, 2013;Utz and Breuer, 2017), between online social support and wellbeing (Lee et al, 2013;Xavier and Wesley, 2018;Ali, 2020).…”
Section: Online Social Support As a Mediatormentioning
confidence: 96%
“…Hence, previous studies have revealed that online social support is associated with an increase in well-being (Lee et al, 2013;Xavier and Wesley, 2018;Ali, 2020). As such, previous studies have confirmed the link between online self-disclosure and online social support (Lee et al, 2013;Utz and Breuer, 2017), between online social support and wellbeing (Lee et al, 2013;Xavier and Wesley, 2018;Ali, 2020). Furthermore, in Korea, a study by Lee et al (2013) on college students reported that online self-disclosure has an indirect effect on well-being through online social support.…”
Section: Online Social Support As a Mediatormentioning
confidence: 96%
“…In turn, the poor health of mothers of children with ASD affects both the development of these children and balance within the family system ( Karst and Van Hecke, 2012 ). Many studies have suggested the importance of social support to the physical and mental health of mothers of children with ASD ( Lu et al, 2015 ; Xavier and Wesley, 2018 ; Zhao et al, 2021 ); such perceived social support helps alleviate their stress, anxiety, depression, and other negative psychological conditions ( Chen S. D. et al, 2021 ; Koukouriki et al, 2021 ; Scheerer et al, 2021 ) and facilitates the enhancement of their parenting competence and the improvement of their wellbeing ( Iadarola et al, 2017 ; Green et al, 2021 ; Khusaifan and El Keshky, 2021 ). Meanwhile, the less social support felt by mothers of children with ASD, the more they suffer from psychological problems such as anxiety and depression ( Smith et al, 2011 ; Huang et al, 2019 ; Bujnowska et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%